2011
DOI: 10.1111/j.1365-2265.2011.04120.x
|View full text |Cite
|
Sign up to set email alerts
|

Serum myostatin levels and grip strength in normal subjects and patients on maintenance haemodialysis

Abstract: The mode of dialyzer modulates the blood levels of myostatin. Higher myostatin is associated with lower muscle function. The use of myostatin assay in various clinical settings merits further investigation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
64
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 71 publications
(76 citation statements)
references
References 38 publications
10
64
2
Order By: Relevance
“…Previously we proposed an “accelerator-brake model” to explain most reported observations in animals and humans. In this model, the expression level of myostatin reflects the endogenous proliferative activity of skeletal muscle and serves as a brake to restrain excessive muscle growth [10]. Consistent with our model, myostatin was previously reported to decrease with age which may parallel the development of sarcopenic obesity in elderly.…”
Section: Introductionsupporting
confidence: 84%
“…Previously we proposed an “accelerator-brake model” to explain most reported observations in animals and humans. In this model, the expression level of myostatin reflects the endogenous proliferative activity of skeletal muscle and serves as a brake to restrain excessive muscle growth [10]. Consistent with our model, myostatin was previously reported to decrease with age which may parallel the development of sarcopenic obesity in elderly.…”
Section: Introductionsupporting
confidence: 84%
“…Otherwise, non-supplement participants may have low protein intake due to the absence of nutrition support and supplement. The expression of myostatin increment to restrict the enhancement of muscle tissue amid the procedure of muscular growth (Han et al, 2011). We did not find any significant relationship between myostatin and the SMI, which may be due to the fact that the dose of myostatin and the myostatin receptor were not well coordinated.…”
Section: Discussioncontrasting
confidence: 42%
“…A previous study suggested that myostatin, which is one of the factors in the ubiquitin proteasome system, might be a potential mechanism of this triangle association. First, higher serum myostatin is associated with lower HGS [21], and lower myostatin is associated with higher HGS [22].…”
Section: Discussionmentioning
confidence: 99%